2021
DOI: 10.1183/13993003.00432-2021
|View full text |Cite
|
Sign up to set email alerts
|

Association of lung clearance index with survival in individuals with cystic fibrosis

Abstract: BackgroundThe lung clearance index (LCI) assesses global ventilation inhomogeneity and is a sensitive biomarker of airway function in cystic fibrosis (CF) lung disease.ObjectivesWe examined the association of LCI with the risk of death or lung transplantation (LTX) in individuals with CF.MethodsWe performed a retrospective analysis in a cohort of individuals with CF aged≥5 years with LCI and FEV1 measurements performed between 1980 and 2006. The outcome was time until death or LTX. We used the earliest availab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…for every increase in LCI z-score and 18% for every decrease in FEV1 z-score, thereby leading the authors to conclude the potential utility of LCI as a novel surrogate marker of survival. 57 Moreover, a 3-year multicenter observational study of repeated LCI measurements demonstrated feasibility and reproducibility over time. 58 PwCF with predominantly mild disease had stable LCI over time, while PwCF with worsening LCI had a higher baseline LCI, increased age, lower baseline FEV1pp, PA infection, and increased number of IV antibiotics courses.…”
Section: Pulmonologymentioning
confidence: 94%
See 1 more Smart Citation
“…for every increase in LCI z-score and 18% for every decrease in FEV1 z-score, thereby leading the authors to conclude the potential utility of LCI as a novel surrogate marker of survival. 57 Moreover, a 3-year multicenter observational study of repeated LCI measurements demonstrated feasibility and reproducibility over time. 58 PwCF with predominantly mild disease had stable LCI over time, while PwCF with worsening LCI had a higher baseline LCI, increased age, lower baseline FEV1pp, PA infection, and increased number of IV antibiotics courses.…”
Section: Pulmonologymentioning
confidence: 94%
“…LCI is an alternate measure of pulmonary function, often used in younger ages. In a single‐center retrospective examination from 1980 to 2006 of 237 patients over age 5, the risk of death increased by 4% for every increase in LCI z‐score and 18% for every decrease in FEV1 z‐score, thereby leading the authors to conclude the potential utility of LCI as a novel surrogate marker of survival 57 . Moreover, a 3‐year multicenter observational study of repeated LCI measurements demonstrated feasibility and reproducibility over time 58 .…”
Section: Pulmonologymentioning
confidence: 98%
“…Its principal read-out parameter, the lung clearance index 2.5% (LCI 2.5 ), detects progression of CF lung disease (13,28). It furthermore correlates with infection with Pseudomonas aeruginosa and airway inflammation and serves as predictor for later spirometry results and survival of patients with CF (13,(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37] The decision to include LCI as a variable in the ECFSPR from 2018 onwards is therefore rather appropriate since it can help to diagnose earlier stage lung disease than if only a decrease in FEV 1 is considered; this has promising implications for future prognostication in CF, as recently presented elsewhere. 38 We hope it is, or will become, available and reimbursed in as many countries as possible.…”
mentioning
confidence: 99%